2007
DOI: 10.1080/13880200601026325
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, Antiprotozoal, and Toxic Activities of Cnidarian Extracts from the Mexican Caribbean Sea

Abstract: Antimicrobial, antiprotozoal, and toxic activities of crude extracts obtained from six cnidarian species [Cassiopea xamachana (R.R. Bigelow, 1892), Carybdea marsupialis (Linné, 1758), Linuche unguiculata (Swartz, 1788), Bartholomea annulata (Leseur, 1817), Lebrunia danae (Duchassaing and Michelotti, 1860), and Stichodactyla helianthus (Ellis, 1768)] from the Mexican Caribbean Sea were studied. The extract obtained from Linuche unguiculata was found to be the most active against the yeast Candida albicans and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Neurotoxic effects were also identified in two of Cassiopea's nematocyst types (birhopaloid and a-isorhiza) (Gülşahin, 2015). The ease at which Cassiopea can be collected globally in mangroves and cultured in the lab, provides a clear advantage to studying this species' venom, which has antitumor and antiprotozoal properties that may serve as future novel pharmacological and therapeutics agents (Orduña-Novoa et al, 2003;Morales-Landa et al, 2007;Mirshamsi et al, 2017). A recent study showed that Cassiopea crude venom induced apoptosis in human breast cancer tissue via reactive oxygen species (ROS) mediated cytotoxicity (Mirshamsi et al, 2017).…”
Section: Toxinology and Cnidomementioning
confidence: 99%
“…Neurotoxic effects were also identified in two of Cassiopea's nematocyst types (birhopaloid and a-isorhiza) (Gülşahin, 2015). The ease at which Cassiopea can be collected globally in mangroves and cultured in the lab, provides a clear advantage to studying this species' venom, which has antitumor and antiprotozoal properties that may serve as future novel pharmacological and therapeutics agents (Orduña-Novoa et al, 2003;Morales-Landa et al, 2007;Mirshamsi et al, 2017). A recent study showed that Cassiopea crude venom induced apoptosis in human breast cancer tissue via reactive oxygen species (ROS) mediated cytotoxicity (Mirshamsi et al, 2017).…”
Section: Toxinology and Cnidomementioning
confidence: 99%
“…Regarding cubozoans, Morales-Landa et al [ 102 ] tested the activity of crude extracts from Carybdea marsupialis (Carybdeida) against bacteria Streptococcus faecalis , B. subtilis , M. luteus , E. coli , K. pneumoniae , Serratia marcescens , S. typhi , and fungi C. albicans ; 10 μg/mL did not produce any damage to microorganisms.…”
Section: Antimicrobials From Cnidariamentioning
confidence: 99%
“…A small amount (2%) of Giardia duodenalis was resistant to the sea anemone venoms. Subsequently, the activity of the extract from the jellyfish Linuche unguiculata against Giardia lamblia (IC 50 = 63.2 μg/mL; 95% confidence interval: 63.3–63.1) was reported [ 102 ]. The same paper reports the antiprotozoal activity of extracts from other cnidarians against Giardia lamblia , but all IC 50 values ( Cassiopea xamachana = 226 μg/mL; Bartholomea annulata = 316 μg/mL; Lebrunia danae = 631 μg/mL; Stichodactyla helianthus = 1338 μg/mL) showed little effectiveness [ 102 ].…”
Section: Antimicrobials From Cnidariamentioning
confidence: 99%
“…However, the antimicrobial activity of such extracts has been little explored. A few reports can be found in the literature about the antiparasitic and antibacterial properties of some cnidarians and even an antimicrobial peptide isolated from Aurelia aurita has been sequenced [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%